RELIGIONS AND RECONCILIATION OF CONFLICTING SOCIOCULTURAL IDENTITIES - E van der Borght (Acta Theologica, 2018)
In the many cases of conflicts co-fuelled by sociocultural identity contestations, religions cannot play the role of reconcilers, because they have become part of the problem through association with one of the contesting parties. This contribution argues that, in order to come to terms with this, religions have to rediscover the reconciliation practices within their traditions, become more critical of their own past reconciliation record, and develop a theology that pays proper attention to the challenges generated by sociocultural identities. The argument is illustrated with an analysis of the role played by Christian churches in South Africa during the apartheid era.